Highly selective colorimetric and fluorescent detection for Hg2+ in aqueous solutions using a dipeptide-based chemosensor1. Issue 69 (29th July 2015) - Park, Jooyoung; In, Byunggyu; Lee, Keun-Hyeung
<x xml:space="preserve">Abstract</x> A dipeptide-based chemosensor selectively and sensitively detected HgII in aqueous solutions by colorimetric change and fluorescent change.